Cloning, characterization and expression of chicken (Gallus gallus Linnaeus) Bone Morphogenic Protein 2 in Pichia pastoris - Teh, Richard Swee Aun (2015)
Bone Morphogenetic Protein 2 (BMP2) is well known with its significant role in bone healing process and oesteogenesis. It was accidentally discovered by Urist in 1965, when he implanted a demineralized bone in the muscle pouch of a rat. Sampath and Reddi (1981) had further confirmed the effect and characteristic of BMP2 protein. Whereby, when BMP2 protein was removed from the matrix, the matrix failed to induce new bone formation and vice versa. Hence, the effect of Recombinant BMP2 has been tested on most of the mammalian host such as, sheep, rabbits, rats and dogs but not much was done on avian system. Therefore, the aim of this study is to detect the presence of BMP2 gene within the avian genome by using PCR-based method. Primers that targeted BMP2 gene within the avian genome was designed based on the gene sequence from National Centre for Biotechnology Information (NCBI). DNA from domesticated chicken was extracted from the primary feathers and further subjected to Polymerase Chain Reaction (PCR) screening. The PCR results showed positive results for BMP 2 gene detection within the avian genome and the PCR results were sent for sequencing. Subsequently, the sequencing results were used to BLAST against the NCBI gene data bank. The sequencing results returned with successful amplification of BMP2 gene from Gallus gallus. The original BMP2 sequence (NM_204358) was then translated into amino acid sequence and sent for codon optimization via codon substitution. Research also has shown that, codon optimization not only resulted in better gene expression but at the same time the expression products could be purified more readily as compared to the native version. Therefore, with gene synthesis method another new nucleotide sequence of BMP2 was synthesized and it consisted of low % of GC content as compared to the native BMP2 gene and had better stability during the expression stage. The new BMP2 gene was then cloned into Pichia pink α-HC plasmid and relabeled as BMP2v2. The reduction of GC% also had direct impact on the annealing temperature of the primers set from 71.6oC reduced to 63oC and non-specific binding as well. The chromogenic results also had further confirmed the presence of BMP2 protein. Therefore, BMP2 protein was successfully cloned and expressed in Pichia pastoris. Whereby, this BMP2 protein could be further applied in clinical application in avian system in the future.